FTO variant, energy intake, physical activity and basal metabolic rate in Caucasians. The HAPIEE study - HUBACEK, J. A. (2010)
The FTO gene variants are the most important genetic determinants of body weight and BMI known so far, but the mechanism of the effect remains unclear. We have analyzed FTO rs17817449 variant (G>T in first intron) in 6,024 adults aged 45-69 years. Dietary intake was calculated from 140-items food frequency questionnaire, physical activity has been assessed using questions on the number of hours spent during a typical week by sport, walking and other activities out of work requiring heavy and medium physical activity and basal metabolic rate was calculated. The FTO variant was significantly associated with basal metabolic rate (Kcal per day and kg of body weight) in females (P = 0.006; GG = 19.3 ± 2.2, GT = 19.5 ± 2.2, TT = 19.7 ± 2.2), but not in males (P = 0.42, GG = 20.9 ± 1.9, GT = 21.0 ± 1.8, TT = 21.1 ± 1.8). Total energy intake, total energy intake in fat, in carbohydrates, in proteins and in alcohol, and performed physical activity were not associated with FTO genotype either in males or females. We conclude that effect of the FTO rs17817449 variant on BMI values in adults is not mediated through the association with energy intake or physical activity, but rather through the effect on basal metabolic rate, and that this effect is more pronounced in females.